Development of Animation Based Arabic Online Learning Media for Arabic Language Education Students of UIN K.H. Abdurrahman Wahid Pekalongan - Akhmad Aufa Syukron; Faliqul Isbah; Muhamad Jaeni; Akhmad Zaeni (2025)
The research aims to develop an effective animation-based Arabic online learning media for Arabic Language Education students, and to determine the level of feasible and valid of the online learning media for Arabic Language Education students of UIN K.H. Abdurrahman Wahid Pekalongan. The research uses the Research and Development (R&D) method with the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 15 students who were selected through random sampling techniques. Data collection was carried out through interviews, observations, questionnaires, and expert validation. The results of the study showed that the developed media obtained a validation score of 4.68 from media experts and 4.74 from material experts who showed the